Uji Aktivitas Antioksidan dan Penetapan Kadar Flavonoid Total Pada Ekstrak Etanol Daun Bandotan (Ageratum conyziodes) dengan Metode DPPH - Mahral Effendi Sembiring; Lydia Br. Barus; Defacto Firmawati Zega; Nurbaiti Br. Singarimbun; Suharni Pintamas Sinaga; Elseria Saragih; Junita Manullang; Parsaoran Pardede; Sahat Sinaga; Helen Anjelina Simanjuntak; Herlina Simanjuntak (Herbal Medicine Journal, 2026)
Daun bandotan, also known as Ageratum conyzoides L., contains flavonoids that may have anti-alami properties. The purpose of this study is to determine the total flavonoid content and anti-oxidant activity of the ekstrak etanol daun bandotan. With 96% ethanol as the pelarut, ekstraksi is carried out using the maserasi method. The DPPH (2,2-difenil-1-pikrilhidrazil) method is used to decrease antioksidan activity by decreasing absorption at 517 nm. To determine the total flavonoid content, spectrophotometry is used as a reference. The study's findings indicate that the antioksidan activity of ekstrak etanol daun bandotan is rather high, with an IC50 of 33,619 μg/mL in the Kadar category. The study's findings indicate that ekstrak etanol daun bandotan can function as an alami antioksidan, with an estimated 33,7938 mg of flavonoids per QE.